As charges de Quinho como contraponto crítico no contexto da infodemia e da Pandemia de Covid-19 - Adriana de Oliveira Petrocchi (2022)
This dissertation intends to describe the textual networks produced by cartoons by cartoonist Quinho as a counterpoint effect of disinformation created during the Covid-19 pandemic context that, according to the Pan American Health Organization, generated a parallel pandemic - an Infodemic - which, consequently, led to the weakening of public health, especially in the Brazilian case. The cartoonist was chosen because of his work in defense of the control of the pandemic and the dissemination of reliable information; the predominantly presence of image in his works and their circulation in various media, using - in parallel with publications on Instagram and in the Estado de Minas newspaper, where he works - other digital media such as Facebook and Twitter. Theg complementary and alternative ways of propagation and circulation of his work reached a diverse audience that manifests itself in the comments surrounding his cartoons. The methodological procedure will initially be bibliographic, around three central axes of this research: disinformation, infodemic/health and cartoon/meme. It will then move to a quantitative documentary base in which Quinho's cartoons will be collected between December 2019 (beginning of the pandemic, as indicated by the World Health Organization) until the Tokyo Olympics, in August 2021 (first major collective event held the consolidation of the vaccine phase, but still under strict sanitary precautions). Then, a qualitative sampling will be established: the cartoons will be organized according to their categorization in four pandemic phases: preparation and alert; containment; sustained streaming and recovery, filtered by the artist's most likes on Instagram. Once the work has been defined for each phase, a verbo-visual analysis will then be presented on the chosen cartoons as well the relation with the textual network close to its temporal arc, considering the news events - represented mainly by the headlines of the press vehicles - the memes in circulation. and the comments on the charges. It is concluded that the power of Quinho´s work analyzed in this work is, on the one hand, a verbal-visual tool to support public health efforts and scientific dissemination and, on the other hand, an opposition to disinformation, especially a blunt criticism of the current Brazilian government's attitude towards the Covid-19 pandemic.